Desigualdade territorial: do Grajaú ao ensino superior, as barreiras da mobilidade no espaço periférico - Silva, Karina Rosa da (Universidade Federal de São Carlos, 2026)
The city of São Paulo offers great opportunities, but it also exposes the deep inequalities faced by those living in its peripheries. In the district of Grajaú, in the far south of the capital, these opportunities coexist with daily hardships stemming from a historical process of occupation, expansion, and segregation, which still raises questions today about the future of its residents. In this context, young people's education is directly affected by instability in food security, housing, mobility, and safety, often losing priority in the face of the need to supplement family income, which contributes to school dropout rates. Given this scenario, the research investigates how young people from Grajaú manage to reach higher education, revealing trajectories marked by obstacles but also by the resilience of the territory, analyzed through the lens of Henri Lefebvre and his discussion of the production of urban space, with the aim of understanding the right to, access to, and persistence in higher education for these young people based on their own experiences and accounts.
Territorial Inequality: from Grajaú to Higher Education, the Barriers of Mobility in Peripheral Space
Keywords: Grajaú; Universidade; Mobilidade; Transporte; Educação; University; Mobility; Transportation; Education; CIENCIAS HUMANAS::GEOGRAFIA::GEOGRAFIA HUMANA::GEOGRAFIA URBANA; 10. Redução das Desigualdades